Integralidade na gestão em saúde? : a voz dos gestores - Silva, Bela Feiman Sapiertein (2012)
The Integrality is a principle and a guideline for the organizaton of the Brazil s Unified Health System (SUS). Its effectiveness goes through a lot of tensions and conflicts involving the understanding of health as a right and the economic logic that affects the health management issue. The municipal health management is challenged to mediate these interests and to produce singular initiatives which contribute to the effective Integrality. This study aims to analyze the Integrality s social representations of Health Managers who work in São Mateus s microregion, focusing in the management practices. We interviewed 16 city health managers using a semistructured questionnaire, presenting topics on their daily work. The methodological approach is the qualitative and quantitative research. The data analysis was realized by Collective Subject Discourse technique, which is based on the social representations theory, and we used Qualiquantisoft software as support. The results are presented from the synthesis-speeches which describe the central ideas and anchors identified in the interviews; these speeches were presented in three interrelated and inseparable directions: a) integrality related to the practices and the work organization; b) integrality related to how the individual is perceived, and c) integrality related to the involvement between worker and user. There is an understanding of the need of integration between health sectors, professionals, State departments and federal instances. There is recognition that health problems go beyond the biomedical concept and that the listening and acceptance practices, and also the involvement between workers and users contribute to Integrality s success. However, even with specific initiatives, we have observed many contradictions which indicate the persistence of assistantial medical model. We point out the difficulties and limitations related to macro-organizational factors and municipal issues. The health managers work with a certain resignation and powerlessness, so their practices reproduce the current context tensions and contradictions, showing weakness in the implementation of integrality on management practices.